1. The problem statement, all variables and given/known data Use the rules of inference to prove the following: (¬p ^ q) ^ (r → p) ^ (¬r → s) ^ (s → t) ) ⇔ t. 2. Relevant equations Rules of Inference I guess. 3. The attempt at a solution Honestly I don't know where to start using the rules of inference. I drew a truth table and proved it was a tautology that way, but I can't see where to use the rules because it's such a long equation. If I could even get the first rule to use I could probably work my way from there. Thanks for any help.